Growth and Yield of Pak Choi (Brassica rapa Subsp. Chinensis) in Responses to Leucaena Leaf-based Liquid Organic Fertilizer - Wati, Dewi Anjasmoro; Fahrurrozi; Inoriah , Entang (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2023)
The uses of liquid organic fertilizer (LOF) have been increasingly practiced in organic vegetable to increase the effectiveness of solid organic fertilizer application. Farmers can produce LOF by using locally available green biomass in the surrounding production areas, including leaves of Leucaena leucocephala (Lam) de Wit. This experiment aimed to determine the best concentration of Leucaena leaf-based LOF on growth and yield of Pak Choi (Brassica rapa Subsp. Chinensis). An experiment was arranged in Randomized Complete Design with seven replicates. Treatments are several concentrations of Leucaena leaf-based LOF, 0%, 25%, 50%, 75% and 100%. Although, the concentration of 50% was likely able to increase shoot length, leaf area and leaf greenness of Pak Choi, but the effects of Leucaena leaf-based LOF on leaf numbers, shoot fresh weight, shoot dry weight, root fresh weight and root dry weight of Pak Choi were insignificant. Consistency effects of Leucaena leaf-based LOF in the production of Pak Choi should be re-evaluated